A new species of the genus Alvinocaris Williams and Chace, 1982 (Crustacea: Decapoda: Caridea: Alvinocarididae) from the Manus Basin hydrothermal vents, Southwest Pacific - Wang, Yan-Rong; Sha, Zhong-Li (Zootaxa, 2017)
One new species of alvinocaridid Alvinocaris kexueae sp. nov. is described from hydrothermal vents on the Manus Basin, Southwest Pacific. This is the fifteenth species in Alvinocaris Williams & Chace, 1982. The new species is easily recognized by the combination of the rostrum distinctively overreaching the distal end of the antennular peduncle, and the armature of its dorsal and ventral margins; the unarmed third abdominal segment, and by the posterior margin of the telson having one triangular tooth medially and 6 pairs unequal spines. It is morphologically most similar to A. brevitelsonis Kikuchi & Hashimoto, 2000 described from Minami-Ensei Knoll, Okinawa Trough, but can easily be distinguished from it by the proportionally longer rostrum, by the dorsal teeth of the rostrum, by the shape of the chela of the first pereiopod, and by the teeth on the fourth abdominal segment. The genetic divergence of COI gene analyzed clearly supports the new taxon.